THE INFLUENCE OF CHILDREN'S LITERATURE ON THE FORMATION AESTHETIC CULTURE OF A PRESCHOOL CHILD - I.V. Onyshchenko (Academy of Cognitive and Natural Sciences, 2008)
The article describes since of aesthetic education of pre-school children, defines the role of child's literature in forming culture of preschool children.